Open up your strategy : making strategy behind closed doors is a prescription for failure when disruptions are coming from all directions - Stadler, Christian; Hautz, Julia; Matzler, Kurt; Eichen, Stephan Friedrich von den (MIT Sloan Management Review, 2021)
Making strategy behind closed doors results in copycat, unimaginative, and biased strategies that often fail. Opening up your strategy-making process to participants from outside the C-suite -- and outside your company -- offers leadership teams access to diverse sources of external knowledge, exposes cognitive biases, and builds the buy-in needed to speed execution. The authors describe the steps leaders must take to successfully implement open strategy at their companies.